El monte tucumano como “teatro de operaciones”: las puestas en escena del poder durante el Operativo Independencia (Tucumán, 1975-1977) - Santiago Garaño (Nuevo mundo - Mundos Nuevos, 2011)
In this paper we want to reflect on how and why in the first place, militants from the Partido Revolucionario de los Trabajadores-Ejército Revolucionario del Pueblo (PRT-ERP) and afterwards on february 1975 the military authorities, built primarily the Tucumán’s mount - a relatively peripheral or marginal place on the national scene - as the center of their militant and repressive strategy, respectively. From the analysis of a series of power “stagings” (Balandier, 1994; Abèlés, 1997), we will show how the mount was built as a “theater” where a conventional “war” of “Independence” reaffirmation was waged, where thousands and thousands of soldiers were mobilized and exalted as a paradigm of the “armed virile people” -under the mandate of life sacrifice and the moral value of heroism.